Skewness, Individual Investor Preference, and the Cross-section of Stock Returns - Lin, Tse-Chun; Liu, Xin (Review of Finance, 2018)
Abstract We find a robust negative relation between skewness/lottery-like features, proxied by maximum return (MAX) over the last month, and future returns for stocks preferred by individual investors. This negative relation is nonexistent for the rest of stocks. We identify stocks preferred by individual investors through bundling ten stock characteristics associated with their stock preferences. The negative relation between MAX and future return is produced by the stocks preferred by individuals that account for less than 5% of the overall market capitalization. Our results are robust to alternative definitions of MAX and lottery-like features such as total, idiosyncratic, and expected skewness.